Experiments in transport related choices: The influence of risk and uncertainty in determining commuters' behaviour with respect to parking alternatives - Angela De Carlo; Angela Stefania Bergantino; Andrea Morone (European Regional Science Association (ERSA), 2013)
Over recent years, parking policy has become a key element of urban transport policy and planning in many countries. The need of urban mobility, mostly guaranteed by private cars, in facts, impacts on the policy and regulations of parking areas. The issue is particularly relevant for work related regular trips. Workers have an inelastic demand for parking spaces and limited alternatives to private transport. Often working places have a car parking area to satisfy workers needs but when this is not provided, it implicitly conditions workers? behaviours. The aim of this research is to analyse the trade-off between parking space availability and cost, in terms of time savings (considering time in terms of foregone earnings). This information is pivotal when designing parking policies in terms of fares, investments and regulation. The cost-opportunity of saving time, having information on the availability of slots closer to the working place, is conditioned by the worker?s income and earnings. Since the pivotal work of Axhausen and Polak (1991), a relevant body of literature has focused on parking behaviour, measuring many different dimensions in terms of travellers? choice of parking type and location. However, the little attention has been devoted to understand how risk and uncertainty influence drivers? behaviours in parking decision. This paper presents two studies addressing this issue. Both aims to collect disaggregate data on travellers? responses to changes in parking attributes and related information. Different components of the parking activity (e.g., general in-vehicle time, parking search time, egress time) are controlled for, in relation to the characteristics of the respondent. In order to avoid heterogeneity in relation to journey purposes we focus on workers? mobility. The first study is carried out using a standard stated preference approach; the second is carried out in a laboratory through the set up of an experiment. The collected data is used to build simple model of consumer?s choice related to parking decision, taking explicitly into consideration both risk and uncertainty. Laboratory?s results are compared to the field-experiment?s outcome in order to identify potential significant differences and, where possible, with existing revealed and stated preference results.
Keywords: C91; C93; D12; R41; 330; parking; stated preference; experimental; risk and uncertainty